2003
DOI: 10.1117/12.532516
|View full text |Cite
|
Sign up to set email alerts
|

15-Gbit/in2recording on a DWDD disc using a land/groove substrate with a red laser enabled by a side-wall annealing process

Abstract: We developed a side-wall-annealing technique for land/groove substrates. By applying this technique to our Domain Wall Displacement Detection (DWDD) Magneto-Optical (MO) recording stack formed on a landlgroove substrate, even with an NA of 0.6 and a wavelength of 660 nm, we realized a density of 15 Gbit/in2 with a sufficiently wide recording tolerance. This density corresponds to a capacity of4.7 GB on a 64 mm disc like MiniDisc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Domain wall displacement detection (DWDD) 1) is an excellent method for achieving high recording density on magneto-optical (MO) disks. Over the past few years, a considerable number of studies have been carried out on DWDD disks using a red laser diode (LD) [2][3][4] and a blue LD. 5,6) Tanaka et al reported two types of DWDD disks, an anneal-less type and a sidewall-annealed type, which enabled a land/groove recording of 15 Gbit/in 2 using a wavelength of 660 nm and a numerical aperture (NA) of 0.6.…”
Section: Introductionmentioning
confidence: 99%
“…Domain wall displacement detection (DWDD) 1) is an excellent method for achieving high recording density on magneto-optical (MO) disks. Over the past few years, a considerable number of studies have been carried out on DWDD disks using a red laser diode (LD) [2][3][4] and a blue LD. 5,6) Tanaka et al reported two types of DWDD disks, an anneal-less type and a sidewall-annealed type, which enabled a land/groove recording of 15 Gbit/in 2 using a wavelength of 660 nm and a numerical aperture (NA) of 0.6.…”
Section: Introductionmentioning
confidence: 99%